Analisis Faktor-Faktor Kritis Sukses (Critical Success Factors) Penerapan Sistem Informasi Desa (SID) di Desa Muaro Pijoan - Jhon Fran Trio Halawa; Hendriyaldi Hendriyaldi; Try Syeftiani (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to analyze the Critical Success Factors (CSF) in implementing the Village Information System (SID) in Muaro Pijoan Village, as part of the broader e-government initiative at the village level. The research employs a descriptive qualitative approach, utilizing interviews, observations, and documentation as data collection methods. The results of the study indicate that the implementation of SID has not been fully optimized due to several key challenges, including limited human resources, inadequate technological infrastructure, insufficient funding, and low community participation. Among these, the most influential factors for the success of SID are the capacity of human resources and the level of support from the local government. The study highlights the importance of improving government policies, enhancing the skills and competencies of human resources, and ensuring that specific budgets are allocated to sustain SID management. Furthermore, the findings suggest that improving the involvement of the community in the SID process is crucial for fostering transparency, accountability, and better governance at the village level. This research provides valuable insights into the necessary steps to improve the implementation of SID and contributes to the understanding of e-government success factors in rural areas.